Religious Integration and Psychological Distress: Different Patterns in Emerging Adult Males and Females - Lace, John W. (Journal of religion and health, 2018)
This study examined differences between male and female emerging adults on low, moderate, and high levels of religious integration in relation to psychological distress. Participants were recruited from undergraduate courses at a religiously affiliated, Midwestern university and completed the integration scale of the Personal Religious Inventory and the Langner Symptom Survey. Due to significantly higher reports of religious integration in female participants, the sample was separated by sex. A significant, negative correlation between religious integration and psychological distress was found only for females. Similarly, females in the low religious integration group reported significantly higher levels of psychological distress than females high in religious integration, while no differences were found among males. This study corroborates previous research suggesting a general link between religion and mental health, but further suggests religious integration and psychological distress are uniquely related for males and females. Possible reasons and future areas of study are noted.